Differing Outcome of Experimental Autoimmune Encephalitis in Macrophage/Neutrophil- and T Cell-Specific gp130-Deficient Mice - Holz, Kristian; Prinz, Marco; Brendecke, Stefanie M.; Hölscher, Alexandra; Deng, Fengyuan; Mitrücker, Hans-Willi; Rose-John, Stefan; Hölscher, Christoph (Frontiers in Immunology, 2018)
gp130 cytokines are differentially involved in regulating the T helper (H) 17-driven pathogenesis of experimental autoimmune encephalomyelitis (EAE), the animal model of human multiple sclerosis. IL-6 directly promotes the development of TH17 cells through the gp130/IL-6R complex. In contrast, IL-27 has been shown to suppress a TH17 immune response by gp130/IL-27Rα-ligation. The IL-27-dependent regulation of a TH17 development could be mediated on the level of CD4 T cells. However, because IL-27 also suppresses the secretion of the TH17-driving cytokines IL-6 and IL 12/23p40 in accessory cells, TH17 immune responses may also be controlled by IL 27 on the level of macrophages and/or neutrophils. To analyse these opposing effects of gp130 engagement on the pathogenesis of EAE, we immunized CD4 T cell-specific gp130-deficient (CD4creposgp130loxP/loxP) and macrophage/neutrophil-specific gp130-deficient (LysMcreposgp130loxP/loxP) mice with the myelin-oligodendrocyte-glycoprotein peptide MOG35-55. Whereas inflammatory immune responses, TH17 differentiation and pathology in CD4cregp130loxP/loxP mice was mitigated, disease progression was eventually enhanced in LysMcreposgp130loxP/loxP mice. Exacerbated disease in MOG35-55-immunized LysMcreposgp130loxP/loxP mice was associated with an elevated development of TH17 cells and increased infiltration of the central nervous system with leukocytes indicating a suppressive role of macrophage/neutrophil-gp130. To further prove IL-6 to be responsible for the control of inflammation during EAE through gp130 on macrophages/neutrophils, we immunized LysMcreposIL-6RloxP/loxP mice. In contrast to LysMcreposgp130loxP/loxP mice, neuropathology in MOG35-55-immunized macrophage/neutrophil-specific IL-6R-deficient mice was not enhanced indicating that the alleviation of EAE through macrophage/neutrophil-gp130 is mediated independently of IL-6. Together, this different pathology in macrophage/neutrophil- and CD4 T cell-specific gp130-deficient mice suggests that gp130 cytokines modulate TH17 inflammation differentially by targeting distinct cell types.